2017
DOI: 10.1007/s00432-017-2346-1
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value and pathobiological significance of Glasgow microenvironment score in gastric cancer

Abstract: GMS can serve as a useful prognostic factor for gastric cancer, and according to GMS, the tumor microenvironment in this cancer type may be partially classified as inflammatory or desmoplastic microenvironment that possesses different pathobiological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…GMS is a combination of TSP and KM grade and a few studies have reported a prognostic role of GMS in some subsets of cancer, including colorectal and gastric cancers. In this study, as TSP was not significantly correlated with survival in patient with high KM grade, the high KM grade, irrespective of TSP, can be classified into GMS 0, as in the previous studies . Lower GMS correlated with favorable clinicopathologic factors and clinical outcome.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…GMS is a combination of TSP and KM grade and a few studies have reported a prognostic role of GMS in some subsets of cancer, including colorectal and gastric cancers. In this study, as TSP was not significantly correlated with survival in patient with high KM grade, the high KM grade, irrespective of TSP, can be classified into GMS 0, as in the previous studies . Lower GMS correlated with favorable clinicopathologic factors and clinical outcome.…”
Section: Discussionsupporting
confidence: 51%
“…High TSP significantly correlated with low KM grade and there were only 7 cases (3.6%) showing high TSP with high KM grade. This finding suggests that tumor stroma may act as a suppressant of host inflammatory reaction to tumor cells , and the inflammatory responses may hinder the formation of tumor stroma . Some studies illustrated that cancer‐associated fibroblasts, which is one of the components of tumor stroma, could interact with host immune cells inducing immune tolerance .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%